Фоточутливість і механізми проходження струму в поверхнево-бар’єрних структурах оксид-Cd0,96Zn0,04Te - Новосад, Олексій; Божко, Володимир; Богданюк, Микола; Божко, Неоніла; Novosad, Oleksiy; Bozhko, Volodymyr; Bohdanyuk, Mykola; Bozhko, Neonila (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Методом термічного окислення в повітряному середовищі монокристалів Cd0,96Zn0,04Te за Т=570 оС отри- мано поверхнево-бар’єрні структури оксид-Cd0,96Zn0,04Te. Досліджено їх стаціонарні вольт-амперні характерис- тики та проаналізовано механізми проходження струму. Показано, що поверхнево-бар’єрні структури оксид- Cd0,96Zn0,04Te проявляють фотовольтаїчні властивості. Особливістю спектрів фотонапруги є один вузький максимум, положення якого відповідає енергії квантів світла hυ≈1,54 еВ, а ширина на половині висоти становить ~120 меВ.; In this work photosensitive oxide-Cd0,96Zn0,04Te surface-barrier structures of Cd0,96Zn0,04Te single crystals with p-type conductivity has been produced and studied. Photosensitive surface-barrier structures were produced by heat-treatment of monocrystalline p- Cd0,96Zn0,04Te plates in the air at temperature near 570 °C for t≈40 min. The stationary current-voltage characteristics of these surface-barrier structures are studied. The current mechanisms and the photosensitivity processes of the structures are being discussed. Rectification coefficient for the best structures, at a voltage close to the cutoff voltage (U0) was ~20. For these structures, the initial portion forward of the current-voltage characteristic is described with the conventional diode equation. The reverse steady-state current-voltage characteristic of oxide-Cd0,96Zn0,04Te surfacebarrier structures follows a power law with the m≈2,6 exponent. On the spectrum of photovoltage, there is one with a narrow peak width at half height of ~ 120 meV. The energy position of the maximum the photovoltage was equal to hυ≈1,54 eV.
The Photosensitivity and Passing Current Mechanisms of Oxide-Cd0,96Zn0,04Te Surface-barrier Structur
Keywords: монокристали,; поверхнево-бар’єрні структури; вольт-амперна характеристика; single crystals; surface-barrier structures; current-voltage characteristics